Online individualised tutor for improving mathematics learning: a cognitive diagnostic model approach - Wu, Huey-Min (Educational psychology (Dorchester-on-Thames), 2019)
Based on a cognitive diagnostic model, an online individualised tutor program was developed in this study. An experiment was conducted in practical educational settings exploring the effectiveness of the online individualised tutor remedial program based on the diagnostic reports of the cognitive diagnostic model. The methodology of this study was a non-equivalent quasi-experimentation design, and the unit- fraction was used as an example in the field experiment. The sample subjects were 84 fourth grade students chosen from the elementary schools. The results showed that the online individualised tutor program outperformed the traditional remedial instruction program. The online individualised tutor program was beneficial for all students, especially for medium- and low-achieving students.